Evaluation of the prescribing patterns, adverse effects, and drug interactions of oral chemotherapy agents in an outpatient cancer center. (October 2019) - Solomon, Jenna M; Ajewole, Veronica B; Schneider, Amy M; Sharma, Manvi; Bernicker, Eric H
Purpose: Although oral chemotherapy offers advantages over intravenous chemotherapy, it creates a unique set of challenges. Potential barriers include treatment complexity, patient responsibility for medication adherence and monitoring, reduced healthcare contact, and increased financial burden. The purpose of this study is to estimate the prevalence of drug-related problems among a sample of patients treated with oral chemotherapy agents. Methods: A single-center, retrospective chart review was conducted on patients prescribed oral chemotherapy at our institution between 1 January 2017 and 31 August 2017. The primary endpoint was the incidence of drug-related toxicities within 90 days of starting treatment. Secondary endpoints included incidence of drug–drug interactions, proportion of patients receiving medication education by a clinical pharmacist, and quantification of issues related to medication access. Results: Charts of 100 patients were reviewed. Median time to oral chemotherapy receipt by the patient from the day the order was written was eight days. Prior to initiating therapy, 27% of patients received education by a clinical pharmacist. Toxicity checks were conducted by the provider at 30, 60, and 90 days for 80%, 65%, and 48% of patients, respectively. Treatment-related toxicities secondary to oral chemotherapy were reported by 79% of patients, with 55% classified as severe. Potential drug interactions were in 55% of the patients. Conclusion: Data from this study have highlighted avenues for pharmacists to make an impact on patients newly started on oral chemotherapy. Opportunities exist to increase patient education, ensure appropriate follow-up, and assess adherence while preventing and managing treatment-related toxicities.